Photoelectrochemical properties of ZnO/BiVO4 nanorod arrays prepared through a facile spin-coating deposition route. (July 2019) - Huang, Xiao; Song, Jian; Wang, Linmeng; Gu, Xiuquan; Zhao, Yulong; Qiang, Yinghuai
Abstract: Monoclinic BiVO4 (m-BiVO4 ) thin films were deposited on the ZnO nanorod arrays (NRAs) for constructing a core/shell composite photoanode, leading to a significantly enhanced photoelectrochemical (PEC) performance. Specifically, the ZnO/BiVO4 NRA sample displayed a photocurrent density of 2.3 mA/cm 2 at 0.6 V vs. RHE under a visible light irradiation (100 mA/cm 2 ), while the value was just 0.9 mA/cm 2 for a ZnO NRA and 0.8 mA/cm 2 for a BiVO4 film. The enhanced PEC activity was mainly attributed to the role of ZnO nanorods as a rapid electron transport pathway, which could be also versified by the electrochemical impedance analysis (including the Nyquist and Mott-Schottky plots). Furthermore, a PEC biosensor was fabricated by using a ZnO/BiVO4 NRA photoanode, leading to an acceptable sensitivity of 450 mA·cm −2 ·M −1 and a detection limit of 0.11 μM, respectively.